Beer, wine, spirits and subjective health. Issue 11 (1st November 1999) - Grønbaek, M; Mortensen, E L; Mygind, K; Andersen, A T; Becker, U; Gluud, C; Sørensen, T I
Abstract : STUDY OBJECTIVE: To examine the association between intake of different types of alcoholic beverages and self reported subjective health. DESIGN: Cross sectional health survey with assessment of intake of beer, wine and spirits (at last non-weekend day), smoking habits, social networks, physical activity, body mass index, educational level, presence of chronic disease, and self reported health. SETTING: WHO Copenhagen Healthy City Survey, Denmark. PARTICIPANTS: 4113 men and 7926 women aged 18 to 100 years. MAIN RESULTS: Of the 12, 039 subjects, 8680 reported their health as optimal, and 3359 reported a suboptimal health. After controlling for the covariates, the relation between total alcohol intake and the proportion reporting suboptimal health was J shaped. Heavy drinkers of any of the three types of alcoholic beverages had a higher prevalence of suboptimal health than non-drinkers. However, only light (1-2 glasses of wine yesterday) and moderate (3-5) wine drinkers had significantly lower odds ratios for suboptimal health–0.72 (95% confidence limits; 0.56 to 0.92) and 0.65 (0.49 to 0.87), respectively–when compared with non-wine drinkers. Moderate beer or spirits drinkers did not differ significantly from non-drinkers of these beverages with regard to prevalence of suboptimal health. Consistently, beer preference drinkers had an odds ratio of 1.50 (1.25 to 1.80) for suboptimal health compared with wine preference drinkers. CONCLUSIONS: A light to moderate wine intake is related to good self perceived health, whereas this is not the case for beer and spirits. The causal relations creating this association are unknown and should be considered when interpreting the relation between different types of alcoholic beverages and subsequent morbidity and mortality.